The Project Based Model Learning and Discovery Learning Towards Critical Thinking Ability Children Aged 5-6 Years - Murti, Widya Sri; Rolina, Nelva (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine (1) the influence of the project-based learning model on the critical thinking skills of 5-6-year-old children , (2) the influence of the discovery learning model on the critical thinking skills of 5-6-year-old children , and (3) the difference in influence between project-based learning and discovery learning models on the critical thinking skills of 5-6-year-old children . This research was a quasi-experimental study with a nonequivalent controls groups design . The population of this study consisted of all students aged 5-6 years in Wangi-Wangi Island, Wakatobi Regency, with a sample of 99 children selected through a purposive sampling technique . The instruments used was an observation questionnaire for children's critical thinking skills . Data analysis techniques included an independent sample t- test with a significance level of 0.05. The results of the study show that (1) there is a significant influence on the application of the project-based learning model on the critical thinking skills of 5-6-year-old children , with a t- value of -24.578 and a Sig . of 0.000 < 0.05, (2) there is a significant influence on the application of the discovery learning models on the critical thinking skills of 5-6-year-old children , with a t- value of -15,304 and Sig . of 0.000 < 0.05, and (3) there is a significant difference in the influence between the project-based learning and discovery learning (DL) models on the critical thinking skills of 5-6-year-old children , with a Sig . Value of 0.000 < 0.05.